Pattern of Congenital Heart Diseases in Children in a Tertiary Care Hospital of Bangladesh - Chowdhury, Md Nahid Islam; Ullah, Md Anayet; Hossain, Md Belal; Islam, S M Shahinul (Journal of Bio-Science, 2023)
The most common congenital anomaly and a major contributor to infant and toddler mortality is congenital heart disease (CHD). Although it has high mortality rate but majority of the cases are asymptomatic during early life and usually discovered during routine checkup. To determine the incidence and pattern of congenital heart disease in children in a tertiary care hospital of Bangladesh. This cross-sectional study was conducted among children aged 1 day to 10 years old with cardiac problems who were hospitalized to the Paediatric department of Rajshahi Medical College Hospital, Rajshahi, Bangladesh from August 2018 to August 2021. Early detection of CHD is possible by thoroughly analyzing heart murmurs, clinical manifestations, and outcomes. The data were analyzed utilizing IBM SPSS (version-23). A total of 3512 children under the age of 10 years were evaluated. Here 1.54% of the patients had a CHD murmur. In this study, the most common type of congenital heart illness was a ventricular septal defect (VSD) (37.05%). Atrial septal defect (ASD) (24.07%) was found second most common CHD. Rapid breathing (63%) and poor growth (44.4%) were major clinical presentation. According to types of murmur among patients, 27(50%) had pansystolic murmur, 15(27.77%) had ejection systolic murmur and 12(22.23%) had continuous murmur. Congenital heart disease is a major health concern for Paediatricians due to its significant health hazards and high mortality rate. Early identification of congenital cardiac disease is crucial for preventing complications, lowering mortality, and for proper therapy. J. Bio-Sci. 30(2): 39-45, 2022